2018
DOI: 10.18632/oncotarget.25049
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating and tumor-associated caspase-4: a novel diagnostic and prognostic biomarker for non-small cell lung cancer

Abstract: Late diagnosis limits therapeutic options and survival rate of non-small cell lung cancer (NSCLC) patients. Therefore the identification of biomarkers represents an emerging medical need.A highly sensitive and specific test was developed to identify/quantify a novel/selective diagnostic biomarker for NSCLC patients, caspase-4. This test was validated by using i) plasma from 125 NSCLC patients and 79 healthy (non-pathological) subjects, ii) plasma from 139 smokers and iii) from 70 chronic-obstructive pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 23 publications
9
33
0
Order By: Relevance
“…Recently, we demonstrated higher circulating levels of caspase-4 in NSCLC patients than healthy subjects (12). In this study we found that caspase-4 is expressed in tumor masses than non-cancerous tissues (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Recently, we demonstrated higher circulating levels of caspase-4 in NSCLC patients than healthy subjects (12). In this study we found that caspase-4 is expressed in tumor masses than non-cancerous tissues (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Wang reported that in patients with gastric cancer, higher expression of CASP4 was associated with better OS [17]. However, Terlizzi et al found that CASP4 overexpression is associated with poor prognosis in patients with nonsmall cell lung cancer [18]. The prognostic signi cance of CASP4 in ccRCC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study we found circulating and tumor-associated caspase-4 as a novel diagnostic, predictive and prognostic biomarker for non-small cell lung cancer (NSCLC) patients [8]. Therefore, according to the altered metabotype of lung cancer patients, the main goal of the actual study was to understand any correlation between caspase-4 and the metabolomic profile of NSCLC patients by using both lung tumor tissues and plasma.…”
Section: Research Papermentioning
confidence: 99%
“…High levels of LDH are widely associated to chronic inflammatory diseases as well as to tumor progression/prognosis [9,10]. In our previous study we found that caspase-4 is a novel diagnostic tool for NSCLC patients [8]. Therefore, we first evaluated the levels of circulating (plasma) LDH in NSCLC patients compared to healthy subjects and then correlated them with circulating caspase-4.…”
Section: High Levels Of Plasma Lactate Dehydrogenase (Ldh) Are Associmentioning
confidence: 99%
See 1 more Smart Citation